P9 Does penicillin allergy exist among children? a retrospective study assessing the prevalence of penicillin allergy among children undergoing a penicillin derivative challenge test in the community, following rash occurring after treatment with a penicillin derivative. (June 2019) - Schechter, Abraham; Bitan, Menachem; Schechter, Yosef; Voltsinger, Tatiana
Abstract : Background rashes are common among children treated with penicillin derivatives. Many are recorded as 'penicillin allergy' without any testing. Aim: This study aimed to demonstrate that most children are not 'allergic' to penicillin and can therefore use penicillin again in the future. In addition, it aimed to demonstrate that the oral penicillin challenge test can be safely performed in the community clinic setting. Methods: In this retrospective study the electronic medical files of 402 study participants, of ages 0–17, were reviewed. The included patients were those flagged as allergic to penicillin, referred to a community allergy clinic between 2011–2018, were evaluated by an allergist, and underwent a penicillin or amoxicillin challenge test. The challenge test results were collected and reviewed for documentation of allergic reactions. None of the children had undergone an allergy skin or blood test prior to the challenge test. In addition, the medical files were reviewed for documentation of later use of penicillin derivatives after the challenge test. Results: Apart from a single vomiting incident during the challenge test, none of the challenge tests elicited any responses. Eighty-two (26%) children who underwent the challenge test, used penicillin again at a later stage. Repeat diagnosis of penicillin sensitivity was recorded for 7 (3%) children, following onset of rash following exposure to penicillin after the challenge test. Conclusions: The vast majority of penicillin allergy diagnoses among children are inaccurate, as the rash appearing during use of the medicine is unrelated to an acute allergic reaction. Viral diseases can be a significant factor underlying these rashes. The oral penicillin derivative challenge test performed in community clinics are safe, and should therefore be preferred for any child presenting late-onset rash during penicillin treatment. Widespread use of this challenge test will assist in reducing extraneous use of broad-spectrum antibiotics and resistance to these drugs.